Portulaca oleracea, a rich source of polar lipids: Chemical profile by LC-ESI/LTQOrbitrap/MS/MSn and in vitro preliminary anti-inflammatory activity. (15th September 2022) - Cannavacciuolo, Ciro; Napolitano, Assunta; Heiss, Elke H.; Dirsch, Verena M.; Piacente, Sonia
Highlights: In depth investigation of purslane showed the occurrence of bioactive polar lipids. LC-MS n analysis putatively identified oxylipins, glyco-, phospho- and sphingolipids. Unusual phytofuranes, phytoprostanes and glucuronosylglicerols were found. Purslane lipid enriched fractions inhibited the NF-kB transcription factor. Purslane lipid enriched fractions induced activation of PPAR-ɣ and Nrf2 pathways. Abstract: Considering the ongoing interest in foods rich in nutrients like polyunsaturated fatty acids and bioactive polar lipids, the chemical and biological investigation of Portulaca oleracea (purslane), a herbaceous plant typically appreciated in Mediterranean and Asiatic diet, was carried out. The LC-ESI/HRMS/MS n analysis of extracts and lipid enriched fractions of purslane edible parts provided a comprehensive polar lipid profile, ranging from linear and cyclic oxylipins to high molecular weight lipids including glycolipids, phospholipids and sphingolipids. The evaluation of the anti-inflammatory potential by in vitro reporter gene assays highlighted the ability of purslane lipid enriched fractions, at a concentration of 20 µg/ml, to inhibit the TNF-α-stimulated NF-kB pathway by 30–40% and to activate PPAR-ɣ and Nrf2 transcription factors to the same extent or more than the positive control, respectively. Altogether, these results encourage to revalue purslane in human nutrition as a source of bioactive polar lipids.